Are there customary rights to plants?: an inquiry among the Baganda (Uganda), with special attention to gender - Howard, Patricia L.; Nabanoga, Gorettie (International Food Policy Research Institute, 2005)
Debates around Common Property Resources and Intellectual Property Rights fail to consider traditional and indigenous rights regimes that regulate plant resource exploitation, establish bundles of powers and obligations for heterogeneous groups of users, and create differential entitlements to benefits that are related to social structures. Such rights regimes are important to maintaining biodiversity and to human welfare; failing to recognize them presents dangers. The case study investigates the gendered nature of informal rights to selected tree and plant species that are distinct from, but related to, customary rights to land and trees, and are embedded in cosmology and social norms.